Implementing learning analytics in higher education: A case study on challenges and requirements - Zine, Abdelkhalek; Kaaouachi, Abdelali (Edelweiss Applied Science and Technology, 2024)
Learning analytics (LA) offers an effective solution for leveraging big data to increase retention rates, reduce quality gaps, improve resource allocation, monitor skills development, and raise graduation rates. To evaluate the potential benefits of this solution, this research explores learning analytics in Moroccan higher education, focusing on the implementation needs and challenges. The methodology is based on qualitative research conducted through 10 interviews with teachers from a multidisciplinary faculty in Nador. The findings of this research reveal that few professors use learning analytics tools on their own initiative. They express a need for guidance, support, and user-friendly tools. Most respondents also mentioned various challenges to adopting learning analytics, such as the inability to align learning analytics with teaching practices, ethical and confidentiality concerns, and limitations in data value, all of which can hinder the effectiveness of learning analytics. Additional challenges include a heavy workload, lack of necessary resources, insufficient technological and pedagogical skills, and difficulties in operating learning analytics tools. Furthermore, managing unorganized data and addressing the heterogeneity of databases and datasets present significant obstacles. Lastly, inadequate preparation on the part of faculty members can impede the full realization of the advantages of learning analytics. To address these challenges, several recommendations have been formulated, including the need for training, guidance, the development of policies, models, and frameworks for the adoption of learning analytics, and the certification of learning analytics tools that are useful and easy to use.